Pengungkapan Anti Korupsi dari Perspektif Corporate Governance - Hayati, Liwa wul; Suma’a, Maya Indriani; Andini, Della Putri; Isra, Irfan Mei; Zaitul, Zaitul (AKADEMIK: Jurnal Mahasiswa Humanis, 2025)
Indonesia still faces serious challenges related to corruption as reported by Transparency International’s website, in 2023, With a score of 34, Indonesia is in 115th position out of 180 countries in the assessment of public sector corruption levels based on the Corruption Perception Index. The low score indicates that the level of corruption in the country is still very high. The purpose of this study is to determine and understand the relationship between corporate governance and disclosure of anti-corruption policies. In this study, corporate governance was measured using four indicators, namely the existence of an independent board of commissioners, gender diversity in the board of commissioners, the existence of foreign commissioners, and the number of members of the board of commissioners. Company size and age are used as control variables in this study, which includes 40 companies listed on the Indonesia Stock Exchange (IDX) during the 2022-2023 period, consisting of 37 state-owned enterprises and 3 non-state-owned enterprises. The purposive sampling method was used in this study to select the sample, which resulted in a total of 28 companies. Regression analysis is used to measure how much influence the independent variable has on the dependent variable. The results of the study show that the existence of an independent board of commissioners does not have a significant impact on the level of disclosure of anti-corruption practices by companies. Although the independent board of commissioners has no effect, this study found that gender diversity, the presence of foreign commissioners, and the size of the board of commissioners significantly increase anti-corruption disclosure. In addition, the size and age of the company are also proven to have the same effect.